Participatory variety slection of cold tolerant rice in the western hills of Nepal - Karki, TB; Koirala, KB; BK, SB (Agronomy Journal of Nepal, 2013)
To verify and up scale promising cold tolerant rice genotypes in the western hills, participatory variety selection (PVS) activities viz; coordinated farmer’s field trials (CFFTs), FFTs prepared from Lumle , farmers’ acceptance tests (FATs), larger plot demonstrations, and upscaling activities were conducted during 2008 to 2009. Yield and yield related parameters considering farmers’ preferences were also recorded and analyzed for PVSs under FATs. In 2008, genotypes NR10481-B-11-1-1-1, NR10479-B-33-2-1-1 and NR10482-B-10-3-2-2 had been preferred by farmers because of high grain yield and desired parameters. In 2008, grain yield of Machapuchhre-3, Chhomrong Dhan, and Lumle 5- 2 over yielded Farmers’ Local (2.2 mt/ha) by 83, 89 and 81%, respectively whereas in 2009, grain yield increment of Machapuchhre- 3, Chhomrong Dhan, Lumle- 2, and Chandannath-3 over Farmers’ Local (2.1 t/ha ) was 98 %, 97%, 1078% and 49 %, respectively. Farmers of upper high hills (>2000-m) and high hills (1500-2000-m) preferred Chandannath-3, Machapuchhre- 3, and Chhomrong Dhan while Lumle-2 was liked by farmers of mid hills (1000-1500-m ). DOI: http://dx.doi.org/10.3126/ajn.v1i0.7545 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.74-79